“Measuring bones”: A cross-disciplinary experiential learning event to increase awareness that math is everywhere - Phillips, Catherine I.; Linsenbardt, Kim; Zocchi, Mary Q. (Frontiers in Education, 2024)
Community colleges serve a substantial percentage of college-age students in the United States, many of whom arrive with negative attitudes towards mathematics, despite there being many STEMrelated fields available to community college graduates. The current paper summarizes the creation of a day-long activity that assists students in developing applied mathematical skills in a format that aligns with the experiential learning theory. Students at a community college in Texas are learning math by engaging with a popular topic, crime scene investigation, through an annual event, established in 2017, called NVCsi. Students interact with hands-on activities that combine forensics, mathematics, and other disciplines. The implementation of the event is described so that other colleges can develop their own experiential learning event. Planned data collection for future event cycles are described, as are limitations and constraints of the NVCsi event with a discussion of planned modifications.